Wildfire and climate change amplify knowledge gaps linking mountain source-water systems and agricultural water supply in the western United States - Barnard, David M.; Green, Timothy R.; Mankin, Kyle R.; DeJonge, Kendall C.; Rhoades, Charles C.; Kampf, Stephanie K.; Giovando, Jeremy; Wilkins, Mike J.; Mahood, Adam L.; Sears, Megan G.; Comas, Louise H.; Gleason, Sean M.; et al. (Agricultural water management, 2023)
Agricultural production in the western United States relies on water supplies from mountain source-water systems that are sensitive to impacts from wildfire and a changing climate. The resultant challenges to water supply forecasting directly impact agricultural producers and irrigation managers who rely on snowmelt and streamflow forecasts for crop selection and irrigation scheduling. To date, much research has focused on source-water system processes and agricultural production separately, but in this short communication we highlight a substantial need for new research connecting these disparate systems to improve forecasting accuracy. We identify key knowledge and data gaps regarding the functioning of source watersheds and their contributions to agricultural water resources with associated uncertainties in the context of wildfire and changing climate. In doing so, we encourage researchers, resource managers, and agricultural producers to consider the interdependency of water supply source and sink relationships through improved observations, monitoring, and modeling to ensure sustainable food production in the western US. [Display omitted] •Wildfire and climate change are affecting water yields of forested river basins dominated by snow melt.•There are substantial knowledge gaps among disparate, but intrinsically linked, mountain and agricultural systems.•Knowledge and data gaps challenge forecasting short- and long-term availability with high confidence.•Better integration of monitoring and modeling among mountain processes and agricultural production is needed.